Does environmental regulation improve residents' health? Evidence from China - Pei, Yunhe; Chen, Hailin; Liu, Zhenhai; Hu, Haozhi (Frontiers in Public Health, 2023)
Environmental pollution is an important factor that harms public health, and environmental regulation is the policy instrument to govern pollution, so what impact does environmental regulation have on the public health? What are the mechanisms? To answer these questions, this paper constructs ologit model and uses China General Social Survey data for empirical analysis. The study found first that environmental regulation has a significant effect on improving the health level of residents, and this effect has been increasing with the passage of time. Second, the impact of environmental regulation on residents' health is different among residents with different characteristics. Specifically, the positive impact of environmental regulation on residents' health is stronger among residents with at least a university degree, residents with urban-registered residences, and residents living in economically developed areas. Third, the mechanism analysis found that environmental regulation can improve residents' health by reducing pollutant emissions and improving environmental quality. Finally, by introducing a cost benefit model, it was found that environmental regulation has a significant effect on improving the welfare level of individual residents and society as a whole. Hence, Environmental regulation is an effective means to improve residents' health, but when implementing environmental regulation, we should also pay attention to its negative impact on residents' employment and income.